Change of sensing vector in the subcutaneous ICD during follow‐up and after device replacement. (19th June 2018) - Bettin, Markus; Rath, Benjamin; Ellermann, Christian; Leitz, Patrick; Bögeholz, Nils; Reinke, Florian; Köbe, Julia; Eckardt, Lars; Frommeyer, Gerrit
Abstract: Background: The subcutaneous implantable cardioverter defibrillator (S‐ICD) has been established as a valuable alternative to transvenous ICD for prevention of sudden cardiac death. The system automatically chooses the optimal sensing vector. However, during follow‐up and especially after device replacement we observed a change of the suggested sensing vector in automatic setup. Therefore, we analyzed frequency and reasons of vector change and its impact on inappropriate shocks (IAS). Material and methods: Between June 2010 and December 2017, a total of 216 patients with S‐ICD ® were included in this analysis. In all patients sensing vectors at the time of implantation, during follow‐up, and after device replacement were investigated. Median follow‐up time was 27.3 ± 25.3 months. Results: A change of the initial vector was seen in 77 patients (35.7%). The most frequent reason for vector change was the postoperative setup in supine and erect position in 54 patients (70.1%). In 12 patients (15.5%), the vector was manually changed due to inappropriate sensing and/or therapies. Routine setup during follow‐up led to automatic vector change in 10 cases (13.0%). In only 1 patient the vector was manually changed due to oversensing in an exercise treadmill test. In 27 patients, the device was replaced due to battery depletion and in 6 of these patients the sensing vector was changed by the automatic setup. Vector change did not have an impact for inappropriate therapies in the follow‐up; only 1 patient received an IAS due to an inadvertent vector change after device replacement. Conclusion: In the present study, a significant number of S‐ICD ® patients had a manual or automatic vector change during follow‐up and after device replacement. The study underlines the importance of a thoroughly performed screening and at least two valuable sensing vectors preimplant. Further studies are needed to evaluate the necessity of a routine automatic setup during follow‐up.